Valorisation territoriale du street art : le cas de la commune d’Abobo (Côte-d’Ivoire) - Ibrahima Sagnon; Hugues Ouattara Teninan; Félix Béchi Grah (EchoGéo)
Street art or urban art is a contemporary artistic movement which brings together all forms of art achieved in streets and public spaces. Since 2000, street art has become young people’s customs in Côte d’Ivoire. Over years, urban art is spreading to reach governments and becomes institutionalized with the implication of the commune of Abobo. Originally, street art gave public spaces a precarious image. It periodically contributes to the valuation of communal territory in its institutionalization phase. From these remarks, it results the problem of illegal appropriation of public spaces through the forms of art. The study aims at revealing the logics which underlie street art institutionalization in the commune of Abobo. This work results in the construction of a citizenship and politicization trajectories through the channel of urban art.